Multi-Objectives Ant Colony System For Solving Multi-Objectives Capacitated Vehicle Routing Problem - Mutar, Modhi Lafta; Mohd Aboobaider, Burhanuddin; Hameed, Asaad Shakir; Yusof, Norzihani; Jabbar Mohammed, Ali Abdul; Alrifaie, Mohammed F. (Little Lion Scientific Islamabad Pakistan, 2020)
As a combinatorial optimization problem, the capacitated vehicle routing problem (CVRP) is a vital one in the domains of distribution, transportation and logistics. Despite the fact that many researchers have solved the problem using a single objective, only little attention has been given to multi-objective optimization. As compared to multi-objectives, the comparison of solutions is easier with single-objective optimization fitness function. In this paper, the following objectives were achieved: (i) in view of the domain of the multiobjective CVRP, the total distance traveled by the vehicles and the total number of vehicles used are reduced, and (ii) in the view of the technique, a multi-objective Ant Colony System is proposed to solve the multiobjective of CVRP based on the experience of sub-paths. The proposed algorithm was evaluated using some standard benchmark problems of CVRP. The results show that the algorithm which has been proposed in this study is highly competitive and quite effective for multi-objective optimization of CVRP